Institutional factors affecting entrepreneurship: A QCA analysis - Pau Sendra-Pons; Irene Comeig; Alicia Mas-Tur (European Research on Management and Business Economics (ERMBE), 2022)
A country's institutional framework plays a crucial role in promoting entrepreneurship, which drives economic growth. Encouraging a minimum level of certainty in ambiguous environments characterized by risk taking is important. Aware of this importance, we analyze the influence of institutional factors on entrepreneurship development. Specifically, we analyze political stability, government effectiveness, regulatory quality, a robust rule of law, the ease of starting a new business, and the ease of obtaining credit. We develop two models to explain the presence and absence of entrepreneurship. To do so, we apply qualitative comparative analysis (QCA) to a sample of 48 countries using data sourced from the Global Entrepreneurship Monitor and the Global Innovation Index. The results show that the effect of institutional factors on the level of entrepreneurship varies according to the socioeconomic characteristics of each country. They suggest that a wide range of institutional configurations lead to the presence or absence of entrepreneurship. Although entrepreneurship can be found in unfavorable institutional environments, future research should examine how to formalize such environments as a standardized institutional configuration to shift from necessity to opportunity entrepreneurship. Achieving this shift is relevant for innovation and economic development.
Keywords: A10; E02; L26; 650; Credit; Economic development; Entrepreneurship; Government; Institutional theory; Regulation